Efeitos da ativina a e da folistatina sobre a apoptose de células estromais do endométrio humano - Larissa Milani Coutinho (2015)
Activin A is a growth factor that stimulates decidualization and is abundantly expressed in endometrial proliferative disorders. Nevertheless, whether it directly affects endometrial cell survival is still unknown. This study investigated the effects of activin A, and its antagonist follistatin, on total death and apoptosis rates and on tumor necrosis factor (TNF) release by human endometrial stromal cells (HESC). We also evaluated the effect of activin A, with and without follistatin, on expression of apoptosis-related genes (Bcl-2, Bax, caspase-3 and caspase-8) in HESC. We performed a controlled prospective in vitro study using primary HESC cultures obtained from healthy reproductive age women (n=11). Cells were treated with medium alone (control) or activin A (25 ng/mL) or activin A (25ng/mL) and follistatin (250ng/mL). Apoptosis and total cell death were measured by flow cytometry, while TNF concentrations in culture media were quantified by ELISA. The expression of apoptosis regulatory genes was assessed by real time PCR. Activin A decreased the percentage of apoptotic/dead cells from 31% to 22% (p<0.05, paired t test) and reduced TNF levels in culture medium by 14%, but there was no linear correlation between TNF release and apoptotic rates. Both effects of activin A were reversed by follistatin. The expression of apoptosis regulatory genes was not significantly different among the groups. These findings indicate that activin A promotes HESC survival, possibly by a TNF-independent pathway. This mechanism may be critical to the actions of activin A upon stromal cell growth and differentiation in physiology and disease.